Antecedents to aggression and the use of coercive measures in inpatient mental health settings: a scoping review protocol - Johan Siqveland; Mette Senneseth; Njål Herman E Sterri; Øyvind Lockertsen; Tonje Lossius Husum; Veronica Lockertsen (BMJ Open)
Objective To investigate the antecedents to episodes of aggression and the use of coercive measures in inpatient mental health settings, organize and explore their relationships and patterns through thematic analysis, identify gaps in the literature and provide insights for future research.Introduction The use of coercive measures in inpatient mental health settings remains controversial and ethically challenging. Despite an international consensus on the need to reduce their use, the antecedents to aggression and episodes involving coercive measures remain insufficiently explored. This review seeks to address this gap by systematically mapping the evidence of these antecedents and exploring their relationship, providing a foundation for future research.Inclusion criteria Studies included were those published from 2014 to the present in the English language, focusing on either adult mental health inpatients or mental healthcare professionals aged 18 years or older involved in episodes of aggression or exposure to coercive measures in both acute and long-term inpatient mental health settings. Included studies must address antecedents to aggression or the use of coercive measures. Exclusions apply to studies focusing exclusively on behaviours unrelated to aggression or coercive measures, studies conducted in non-inpatient settings and those involving child, adolescent, geriatric or forensic populations.Methods The review will follow the Joanna Briggs Institute methodology for scoping reviews. The search strategy will cover key databases, including Ovid Medline, APA PsycINFO and Scopus, with reference list screening to ensure comprehensive coverage. Initial exploratory searches were conducted in June 2024, with the formal searches updated in January 2025. Studies will be screened against the inclusion criteria, and data will be extracted using a standardised form adapted to the review objectives. Grey literature will be excluded, focusing on peer-reviewed evidence. The analysis will include descriptive mapping of the antecedents to aggression and the use of coercive measures, supplemented by thematic analysis to organize and explore patterns and relationships between them. Results will be presented in a descriptive summary, supported by thematic analysis and descriptive statistics.Ethics and dissemination Ethical approval is not required since this study uses existing published literature. The results will be disseminated through a peer-reviewed journal and presented at relevant international conferences.